Optical properties of the porous glass composite material - Ovechko, Volodymyr; Schur, Olexander; Mygashko, Valentyna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Spectrum absorption and luminescence methods were used to investigate the peculiarities of optical properties of compound material consisting of nanoporous silica with impregnated gold nanoparticles soaked in rhodamine 6G ethanol solution. One possible explanation for the phenomenon of increasing of absorption near plasmon resonance frequency and rhodamine 6G absorption band is given.
Optica Applicata, Vol. 38, 2008, nr 1, s. 75-82
Keywords: optyka; porous silica; gold nanoparticles; dye; absorption; luminescence; rhodamine 6G